Low linoleic acid foods with added DHA given to Malawian children with severe acute malnutrition improve cognition: a randomized, triple-blinded, controlled clinical trial. Issue 5 (2nd November 2021) - Stephenson, Kevin; Callaghan-Gillespie, Meghan; Maleta, Kenneth; Nkhoma, Minyanga; George, Matthews; Park, Hui Gyu; Lee, Reginald; Humphries-Cuff, Iona; Lacombe, R J Scott; Wegner, Donna R; Canfield, Richard L; Brenna, J Thomas; et al.
ABSTRACT: Background: There is concern that the PUFA composition of ready-to-use therapeutic food (RUTF) for the treatment of severe acute malnutrition (SAM) is suboptimal for neurocognitive recovery. Objectives: We tested the hypothesis that RUTF made with reduced amounts of linoleic acid, achieved using high-oleic (HO) peanuts without added DHA (HO-RUTF) or with added DHA (DHA-HO-RUTF), improves cognition when compared with standard RUTF (S-RUTF). Methods: A triple-blind, randomized, controlled clinical feeding trial was conducted among children with uncomplicated SAM in Malawi with 3 types of RUTF: DHA-HO-RUTF, HO-RUTF, and S-RUTF. The primary outcomes, measured in a subset of subjects, were the Malawi Developmental Assessment Tool (MDAT) global z -score and a modified Willatts problem-solving assessment (PSA) intention score for 3 standardized problems, measured 6 mo and immediately after completing RUTF therapy, respectively. MDAT domain z -scores, plasma fatty acid content, anthropometry, and eye tracking were secondary outcomes. Comparisons were made between the novel PUFA RUTFs and S-RUTF. Results: Among the 2565 SAM children enrolled, mean global MDAT z -scores were –0.69 ± 1.19 and –0.88 ± 1.27 for children receiving DHA-HO-RUTF and S-RUTF, respectively (difference 0.19, 95% CI: 0.01, 0.38). Children receiving DHA-HO-RUTF had higher gross motor and social domain z -scores than those receiving S-RUTF. The PSA problem 3 scores did not differ by dietary group (OR: 0.92, 95% CI: 0.67, 1.26 for DHA-HO-RUTF). After 4 wk of treatment, plasma phospholipid EPA and α-linolenic acid were greater in children consuming DHA-HO-RUTF or HO-RUTF when compared with S-RUTF (for all 4 comparisons P values < 0.001), but only plasma DHA was greater in DHA-HO-RUTF than S-RUTF ( P  < 0.001). Conclusions: Treatment of uncomplicated SAM with DHA-HO-RUTF resulted in an improved MDAT score, conferring a cognitive benefit 6 mo after completing diet therapy. This treatment should be explored in operational settings. This trial was registered at clinicaltrials.gov as NCT03094247. Graphical Abstract: